Identification and Characterization of Small‐Molecule Inhibitors to Selectively Target the DFG‐in over the DFG‐out Conformation of the B‐Raf Kinase V600E Mutant in Colorectal Cancer. Issue 10 (14th September 2016) - Yao, Huixiang; Sun, Qun; Zhu, Jinshui
Abstract : V600E is the most common mutation in the B‐Raf kinase domain and the B‐Raf V600E mutant has been recognized as an attractive target of colorectal cancer. Here, the structural dynamics of V600E‐induced conformational conversion in the B‐Raf activation loop (A‐loop) was characterized in detail using a computational simulation strategy. The simulations revealed that the V600E mutation would induce A‐loop flipping from DFG‐out to DFG‐in, and the approved B‐Raf inhibitor vemurafenib exhibits strong selectivity for the mutant over the wild‐type kinase. The selectivity is closely associated with the kinase conformation, which can be influenced directly by the V600E mutation. The molecular structure of vemurafenib was applied to a chemical similarity search against a large library of drug/lead‐like compounds, from which three hits with high structural similarity were identified, and their inhibitory activities against both the wild‐type and mutant kinases were measured by in vitro kinase assay, from which two compounds were determined to possess higher selectivity for the B‐Raf V600E mutant than for the wild type (5.2‐ and 3.1‐fold, respectively). They can potently inhibit the kinase mutant with IC50  = 54 and 76 nM, respectively. Structural analysis suggested that specific noncovalent interactions play a crucial role in the selectivity of B‐Raf inhibitors. Abstract : The structural dynamics of the V600E‐induced conformational conversion in the B‐Raf activation loop is characterized in detail using a simulation strategy. Mutant‐selective B‐Raf inhibitors are identified based on the harvested knowledge and confirmed by kinase assay.